Chapter 7: The Treaty of Waitangi and Social Well-being: Justice, Representation, and Participation - Sullivan, Ann (Waitangi Revisited, 2005)
Keywords: crown; elections; government relations; history; land tenure; local government; māori electorates; māori seats; parliament; race relations; social justice; tiriti o waitangi/treaty of waitangi; treaty principles; voting

Māori wards and advisory boards - Bargh, Maria (Local Government in New Zealand: Challenges & Choices, 2016)
Local government in New Zealand faces major challenges. Among the most pressing are continual legislative change, threats to its autonomy, the gradual erosion of community voices in council planning and decision-making, and the need for funding solutions to ensure property rates remain affordable. As well, there is an urgent need for a more coordinated approach across central government on major policy issues such as climate change and housing. This book exposes these challenges and proposes and debates solutions for the future of our local government. Strong local government is vital for ensuring economic growth across and within regions and local communities, for enhancing community wellbeing, for funding and providing the infrastructure needed for, in some cases, rapidly growing and diverse communities, for ensuring our environment is valued and protected, and for planning for development in a time of constraint on resources. This book is a 'one-stop information shop' on local government that can be used by those who regularly interact with or study this area of government, by those working within local authorities, and by those who actively work to ensure their communities grow in a sustainable way.
Keywords: local government